Key players: Space as object of and resource in processes of change - Gailing, Ludger; Ibert, Oliver (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
With the notion of key players the authors tackle a major conceptual problem in recent debates on socio-spatial change. How can we conceptualize socio-scientifically what perceived wisdom among practitioners frequently maintains: the decisive role of single persons in complex processes of change? This paper seeks to identify socio-scientific concepts from several disciplinary strands, mainly from political sciences, organization and management studies and sociology that are helpful for defining key players and for understanding their contribution to processes of change. Furthermore, the authors elucidate heuristically in how far the influence of the types “leader”, “intermediary” and “governance pioneer” can also be explained in terms of how they act in space and how they mobilize spatially distributed resources. Space, it is argued, can be understood as an object of change and as a resource in processes of change.